Participation of the Village Development and Security Committee Members in Community Development Programmes in Kuching, Sarawak - Mohd Hassan, Munirah (1997)
The need to strengthen the Village Development and Security Committee (VDSC) members as the primary machinery for the participation of the people in development programmes has been a concern in the State of Sarawak in its attempt to improve and develop the rural sector. The Kuching District Office in its survey on the participation of VDSC members in community development programmes found that their involvement in the programmes were low. Hence, the purpose of this study was to determine factors associated with the participation of Village Development and Security Committee (or locally referred to as JKKK) in community development programmes in Sejingkat area of Kuching District, Sarawak, East Malaysia. Data for the study were solicited from 123 VDSC members from 12 villages through personal interview using a structured questionnaire. The data were analysed by using a simple frequency distribution for all the variables in the study. Pearson Correlation was used to determine the association between participation in development programmes and selected demographic variables, understanding of their functions as VDSC members and exposure to information on development programmes. The findings of the study revealed that income, age, length of stay in their village, understanding of functions and exposure to information indicate a positive correlation with participation. It was found that frequency of dissemination of information on development programmes was the most significant variable (r=.65), followed by understanding of their functions (r =.60). The findings of the study also revealed that the frequency of participation of the VDSC members in the process of developing the programmes were low. It was concluded that the VDSC members as leaders at the grassroot level must be competent and possess the necessary management skills in order to be able to participate actively in development programmes. Suggestions made include a systematic training programmes to be developed for the VDSC members in order to acquaint them with their functions as grass root leaders and be able to participate actively in development programmes. It is also suggested that more information channels should be opened to disseminate information on development programmes which is accessible to the VDSC members especially in those villages where there are limited sources of communication network.